Documentary and creativity of radio features by Katarzyna Michalak and Marta Rebzda - Bachura-Wojtasik, Joanna; Sygizman, Kinga (Methods of communication and media researches. Theoretical and analytical perspective, 2021)
The chapter analyzes audio narratives: radio plays, documentaries, features by Katarzyna Michalak and Marta Rebzdy, based on the category of artistic processing of facts and classification of editing. It answers the question about the authors' attitude to facts and indicates the relations in which documentary and fictional elements remain. The creative organization of the audio material may take various forms, determined by the content of the story and the author's idiostyle.